2016
DOI: 10.1016/j.addbeh.2016.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Life adversity is associated with smoking relapse after a quit attempt

Abstract: Multiple cross-sectional studies have linked adverse childhood events and adult adversities to current smoking, lifetime smoking, and former smoking. To date, however, there have been no direct observation studies assessing the influence of adversities on smoking relapse. We prospectively followed 123 participants, 86 of whom were habitual smokers, from pre-quit ad libitum smoking to four weeks post quit. Thirty-seven non-smokers were also tested in parallel as a comparison group. Subjects provided biological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 73 publications
(101 reference statements)
2
5
1
2
Order By: Relevance
“…These results extend previous findings from our, as well as others’, laboratories, which indicate that early adversity increases an individual’s risk of early smoking initiation and lifetime smoking (Edwards et al 2007; Ford et al 2011; Lemieux et al 2016; Topitzes et al 2010; Walsh and Cawthon 2014). To that end, it is important to note that a high level of early adversity was associated with higher withdrawal and distress in this study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results extend previous findings from our, as well as others’, laboratories, which indicate that early adversity increases an individual’s risk of early smoking initiation and lifetime smoking (Edwards et al 2007; Ford et al 2011; Lemieux et al 2016; Topitzes et al 2010; Walsh and Cawthon 2014). To that end, it is important to note that a high level of early adversity was associated with higher withdrawal and distress in this study.…”
Section: Discussionsupporting
confidence: 91%
“…To that end, it is important to note that a high level of early adversity was associated with higher withdrawal and distress in this study. Consistent with this finding, a recent study with a larger sample of smokers found that individuals who relapsed earlier reported higher level of early adversity (Lemieux et al 2016). This study was also partially consistent with another study that showed a relationship between early adversity and smoking initiation (van Loon et al 2005).…”
Section: Discussionsupporting
confidence: 64%
“…Esses dados são de grande relevância, visto que, para obter os resultados esperados com as políticas de controle do tabaco, devem ser abordadas as questões emocionais dos tabagistas com mais ênfase, sendo necessário, para isso, um maior preparo da equipe do programa, que terá um papel fundamental no tratamento. Um estudo descreveu os transtornos emocionais como anomalias para as equipes de ESFs, que se encontram despreparadas para o acolhimento dos pacientes que apresentam tais patologias, por estas fugirem da prática comum das equipes, que funcionam numa lógica biomédica, e por demandarem uma atenção mais individualizada e capacitada desses profissionais de saúde (31) .…”
Section: Discussionunclassified
“…As pessoas que buscam pelos serviços de saúde, muito mais que a queixa inicial que apresentam, trazem consigo outras questões que precisam ser observadas para que esse serviço tenha real eficiência. Fica evidenciado que os profissionais de saúde precisam estar preparados, por meio de formação adequada e permanente, para se lidar com as diferentes necessidades apresentadas no cuidado do paciente tabagista, a fim de oferecer um serviço mais integral e resolutivo (31) .…”
Section: Discussionunclassified
“…Low HPA reactivity and high nicotine craving predicts relapse in men but high HPA reactivity predicts relapse in women (al’Absi et al, 2015). Further, relapsing women report a higher adversity than abstinent women (Lemieux, Olson et al 2016). Thus, sex may also be an important moderator of both stress reactivity and smoking related outcomes in the context of ELA.…”
Section: Introductionmentioning
confidence: 99%